LGG-04. MULTIOMIC ANALYSIS OF MAPK PATHWAY ACTIVITY IN PEDIATRIC PILOCYTIC ASTROCYTOMA. (1st June 2021) - Sigaud, Romain; Selt, Florian; Hielscher, Thomas; Stefanski, Anja; Overbeck, Nina; Usta, Diren; Kocher, Daniela; Remke, Marc; Picard, Daniel; Pfister, Stefan M; Jones, David T W; Brummer, Tilman; et al.
Abstract: Introduction: Pilocytic astrocytomas (PA) are the most common pediatric brain tumors. They are characterized by MAPK pathway alterations, leading to its constitutive activation and modulating the balance between cell proliferation and the oncogene-induced senescence (OIS) sustained by senescence-associated secretory phenotype (SASP) factors. This makes PA suitable for MAPK inhibitor (MAPKi) therapies, showing encouraging results in phase 1/2 clinical trials. Little is known about the molecular implications of MAPK downregulation in the proliferating and senescent compartments. Methods: DKFZ-BT66 PA cells derived from a primary KIAA:BRAF-fusion positive PA cell line, were used as model system. Gene expression and phospho-proteomic datasets were generated from DKFZ-BT66 cells, in both the proliferative and senescent states, and treated with the MEKi trametinib for different time-spans. A time course analysis based on differentially expressed genes was performed, followed by a single-sample gene set enrichment analysis (ssGSEA). Analysis of the phospho-proteomic data is ongoing. Results: Differential gene expression analysis revealed that MEK inhibition leads to the inhibition of the OIS-SASP gene program in senescent DKFZ-BT66. ssGSEA showed that most MAPK-related signatures were downregulated upon MEKi treatment, while pathways related to upstream MAPK activators (including FGFR, NTRK and TGFB pathways) were upregulated, in both proliferating and senescent DKFZ-BT66. Genes regulated by the MAPK pathway and involved in OIS-SASP were identified by analyzing genes differentially regulated between proliferating and senescent DKFZ-BT66, and modulated upon MEKi treatment. Conclusion: This data suggests that MAPKi reverses OIS in senescent PA cells, while inducing the activation of MAPK upstream regulators in proliferating and senescent PA cells, identifying putative co-targets that could help prevent growth rebound upon MAPKi withdrawal. Furthermore, the identification of the MAPK-related OIS-SASP genes provide insight about the regulation of OIS-SASP by the MAPK pathway. Validation of this data with the ongoing phospho-proteomic analysis and in primary samples is needed.